NOTES TO THE CONCEPT OF DECENTRALIZATION - Alper Ozmen (European Scientific Journal, ESJ, 2014)
The concept of decentralization refers to decentralized, directed fromcenter to periphery, organized around and such. This concept, expressed asthe transfer of authority from the center to subordinate ends, is importantboth for more effective and productive management of the areas outside thecenter organization in public administration and for strengthening these areasin terms of democracy conception. Because of the increasing interest all overthe world in issues such as ensuring service–need compliance, theimportance of decisions made by the closest unit to the public and thereduction of bureaucratization have made implementation of decentralizedsystems a necessity in local regions. In this study, conceptual definitionsregarding decentralization and information about its aspects as well as theeffects of political and administrative decentralization on unitary structureswill be presented.